Cost-effectiveness analysis of sintilimab plus chemotherapy for advanced or metastatic esophageal squamous cell carcinoma - You, Maojin; Huang, Yufan; Cai, Zhongjie; Wu, Qingfeng; Zhu, Wei; He, Ying; Chen, Ruijia (Frontiers in Oncology, 2022)
Background: Sintilimab plus chemotherapy (SIDCHM) is more effective than placebo plus chemotherapy (PLCHM) for advanced or metastatic esophageal squamous cell carcinoma (ESCC). However, considering the high cost of sintilimab, this study evaluated the cost-effectiveness of SIDCHM in comparison with PLCHM for advanced or metastatic ESCC from the Chinese healthcare system perspective. Methods: Polymorphic Markov models were constructed to simulate the course and cost of SIDCHM. Treatment drug costs were calculated at national list prices and clinical data, other costs, and utility values were extracted from the reference literature. Primary outcomes included quality-adjusted life-years (QALYs) and incremental cost-effectiveness ratios (ICERs). The robustness of the model was verified by one-way sensitivity analysis and probabilistic sensitivity analysis (PSA). Results: SIDCHM obtained 1.03 QALYs at $24,044.49, whereas the effectiveness and cost of PLCHM were 0.67 QALYs and $14,166.24, respectively. The ICER for SIDCHM versus PLCHM was $23,458.08/QALY. The utility of the PFS state was the parameter that had the greatest effect on the ICER. The PSA showed that SIDCHM had an 86% probability of being cost-effective at the willingness-to-pay threshold of 3* Chinese gross domestic product per capita ($37,653/QALY). Conclusion: From the Chinese healthcare system perspective, SIDCHM is considered a cost-effective treatment option compared with PLCHM as first-line therapy for advanced or metastatic ESCC.